WAKAF PROPERTY OWNERSHIP STATUS: COMPARATIVE STUDY OF THE HANAFI MAZHAB AND THE SYAF'I MAZHAB - Ikhsan, S.Sy., MH (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
A comparative study between the Hanafi School and the Shafi'i School in the context of waqf property ownership shows interesting differences in the views of Islamic law regarding the transfer of ownership and management of waqf property. Nevertheless, both schools of thought try to manage waqf assets with the aim of providing optimal social and religious benefits in accordance with Islamic values. The aim of this research is to determine the ownership status of waqf assets from the perspective of the Hanafi school and the Syafi'i school. This type of research uses library research , while the data collection technique used by the author is by identifying themes or discourse from journals, theses from previous research results, the web (internet), or also taken from other information related to the theme of this research to Look for things in the form of notes, newspapers and so on that are related to the research focus. The results of the research show that according to Abu Hanifah, waqf is the custody of an object which, according to the law, remains the property of the wakif in order to use its benefits for good, whereas according to the Syafi'i school of thought, the position of waqf assets as permanent assets that cannot be withdrawn is based on reasons. legal certainty for waqf recipients so that waqf assets can be used freely and are not tied to time. The main difference between the Hanafi School and the Syafi'i School lies in when the ownership of waqf assets is transferred. The Hanafi School states that the waqif has absolute ownership rights before the waqf is made, while the Syafi'i School believes that ownership immediately transfers to Allah SWT once the waqf is pronounced